Reflections on the causes, effects and legal mechanisms for the control of environmental pollution in Nigeria (2010)
This article is a reflection on the causes, effects and various legal mechanisms put in place for the control of environmental pollution in Nigeria. For the purpose of legal exposition, the article will examine the types and sources of environmental pollution. In view of the consequences of environmental pollutions on both human and animals, the article outlines local legislation and specific international treaties and conventions to which Nigeria is signatory to control environmental pollution. In conclusion, this article makes suggestions aimed at guiding against environmental pollution.